Nightshade & oak - O'Neill, Molly (Fantasy fiction author) (Orbit, 2026)
An Iron Age goddess must grapple with becoming human in this delightful historical fantasy of myth and magic from the author of the instant hit Greenteeth. When Malt, the goddess of death, is accidentally turned human by a wayward spell, she finds she's ill-equipped to deal with the trials of a mortal life. After all, why would a goddess need to know how to gather food or light a fire? Unable to fend for herself, she teams up with warrior Bellis on a perilous journey to the afterlife to try to restore her powers. Frustrated by her frail human body and beset with blisters, Malt might not make the best travelling companion. But as animosity slowly turns to attraction, these two very different women must learn to work together if they are to have any hope of surviving their quest.